Interrelationship between number of flowers, fruits, and cucumber production (Cucumis sativus) grown on a mixture of soil and chicken manure - YUSUF LA’LANG LIMBONGAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Limbongan YL. 2023. Interrelationship between number of flowers, fruits, and cucumber production (Cucumis sativus) grown on a mixture of soil and chicken manure. Biodiversitas 24: 3448-3453. This study aimed to determine the effect on the relationship between the number of flowers, fruits formed and the production of cucumber (Cucumis sativus L.) in chicken manure-supplemented soil. The research was conducted from June to August 2022 in Tikala Village, Tikala Sub-district, North Toraja District, South Sulawesi, Indonesia, at an altitude of 866.9 m above sea level with climate type B (Schmidt and Ferguson) and was arranged in a randomized complete block design (RCBD). The treatment used chicken manure at five levels, namely, control, 100 g, 200 g, 300 g, and 400 g chicken manure per plant. The results showed that the application of chicken manure at different doses gave different responses to the growth and production of cucumbers. A dose of 400 g/plant is the best treatment to increase the number of flowers, number of fruits, size, and production of the fruit up to 54 days after planting, with a fruit weight of 2.69 kg per plot or 17.93-ton ha?1. The number of flowers, number of fruits, fruit diameter, and fruit length had linear responses and a significant positive correlation with the production of cucumbers.